Burnout Syndrome in frontline health care professionals against Covid-19 (Research, Society and Development, 2022)
Objective: To identify Burnout Syndrome in frontline health professionals against Covid-19. Methodology: Cross-sectional carried out with 48 health professionals who worked directly on the front lines against Covid -19 for more than 30 days, in a hospital in the interior of Minas Gerais. The Oldenburg Burnout Inventory (OLBI) scale was used to assess the presence of Burnout Syndrome. Results: 54.2% of professionals showed signs of Burnout Syndrome, 27.1% professional burnout and 18.8% did not show signs of burnout. Most professionals who showed signs of syndrome are female and are not in a marital relationship; they have no other employment relationship, work up to 40 hours a week, hold a mid-level job, receive up to two minimum wages per month, have been on the front line for more than a year and have not been infected by Covid-19. Conclusion: Although there was no statistically significant association between sociodemographic and professional variables and the occurrence of signs of Burnout Syndrome, it is expected that the results of the study in question serve as subsidies for the formulation of institutional policies in order to minimize the negative effects caused by the pandemic on the mental health of its employees.